Polyelectrolyte multilayers for enhancing cell adhesion and potential applications in tissue engineering - Muzzio, Nicolás Eduardo (2018)
Polyelectrolyte multilayers (PEMs) assembled by de Layer by Layer (LbL) technique offer multiplepossibilities for surface engineering as an alternative to covalent chemistry. PEMs have recently attractedattention as a mean to engineer scaffolds and implants to make their interface with tissue more amenablefor cell adhesion, migration and differentiation. In this review we will present the state of the art on theuse of polyelectrolyte multilayers for enhancing cell adhesion. In particular, we will show the differentapproaches followed in our group combining synthetic and bio polymers, and the use of thermalannealing.